DESIGN AND DEVELOPMENT OF A PROTOTYPE FROM RECYCLED PACKAGING - Inche M., Jorge (2003)
This work deals with Tetra-Pak cartons waste, and with the development of a board-shaped commercial prototype. A comparative analysis of technical specifications related to such 30x30x1 cm. size wooden-board is shown.